51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-515
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Recovery-Based Discontinuous Galerkin Method for Turbulence Simulations

Abstract: Discontinuous Galerkin (DG) methods have recently received much attention because of their portability to complex geometries, scalability in parallel architectures and relatively simple extension to high order. However, their implementation for compressible turbulence problems is not straightforward, e.g., due to parameter-free limiting for orders greater than first and the lack of a consistent high-order diffusion scheme for DG. To address this last point, Van Leer proposed the idea of recovery-based disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The TGV was one of the problems in the 1st, 2nd and 3rd International Workshops on High-Order CFD Methods [38][39][40]) and is considered to be a challenging test for high-order methods. Various authors have used high-order discontinuous methods on the TGV test case with excellent results, including classical DG [5,36,37], DGSEM [9,29] and a preliminary study by Bull and Jameson using the FR-SD scheme [41]. Wang gives a review of the current status of high-order methods for several problems including the TGV [1].…”
Section: The Taylor-green Vortexmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGV was one of the problems in the 1st, 2nd and 3rd International Workshops on High-Order CFD Methods [38][39][40]) and is considered to be a challenging test for high-order methods. Various authors have used high-order discontinuous methods on the TGV test case with excellent results, including classical DG [5,36,37], DGSEM [9,29] and a preliminary study by Bull and Jameson using the FR-SD scheme [41]. Wang gives a review of the current status of high-order methods for several problems including the TGV [1].…”
Section: The Taylor-green Vortexmentioning
confidence: 99%
“…Gassner [9], Diosady and Murman [29], Chapelier et al [5], Don et al [35], Johnsen et al [36] and Carton de Wiart et al [37]. The TGV was identified as a challenging problem for high-order methods in the 1st, 2nd and 3rd International Workshops on High-Order CFD Methods [38][39][40].…”
mentioning
confidence: 99%
“…The reader is referred to past work on this topic for additional information. 12,13 A. Combining DG and MUSCL Using Recovery for the diffusive terms, accuracy of the order 3p + 2 in the cell-average of the conservative quantities are readily achieved by using information from the neighboring cells.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…In past work,, 12 it could be observed that, while kinetic energy and enstrophy were well resolved already on grids of 64 3 with the standard approach for advection, dilatation was not. It is interesting to note that such a feature has been observed with other approaches for compressible turbulence.…”
Section: B Compressible Turbulencementioning
confidence: 95%
See 1 more Smart Citation